Depositional environment and climate changes during the Holocene in Grande Valley, Fildes Peninsula, King George Island, Antarctica. Issue 6 (13th September 2017) - Chu, Zhuding; Sun, Liguang; Wang, Yuhong; Huang, Tao; Zhou, Xin
Abstract: A 9.24 m sediment core, GA-2, was collected on the coastal platform of Grande Valley, a relatively narrow and shallow fjord in Fildes Peninsula, King George Island, Antarctica. The sediment was formed between 6600 and 2000 cal. yrbp according to accelerator mass spectrometry (AMS) 14 C dating of five bulk sediment samples. The comprehensive proxy indicators (grain size, loss on ignition at 550°C, magnetic susceptibility, elements) were analysed, and three separate depositional environments and an alternating climate change pattern were identified. Grande Valley experienced a warm marine environment between 6600 and 5800 cal. yrbp, a minor cooling between 5800 and 4800 cal. yrbp, the transition from cool to warm during 4800–4400 cal. yrbp, a mid-Holocene climatic optimum between 4400 and 2700 cal. yrbp, and the onset of the Neoglacial at 2700 cal. yrbp . This study reconstructed the environmental history of Grande Valley during the mid–late Holocene, provides the missing marine record of historical climate for the western coast of Fildes Peninsula and lays the foundation for further study of the climate and environment changes therein. Our finding that the sea level was c. 12 m a.m.s.l. at 2000 cal. yrbp allows for detailed reconstruction of Holocene sea level variations.